Comprehensive characterization of sortase A‐dependent surface proteins in Streptococcus mutans. (22nd February 2022) - Katsumata, Tamaki; Nguyen‐Tra Le, Mi; Kawada‐Matsuo, Miki; Taniguchi, Yuri; Ouhara, Kazuhisa; Oogai, Yuichi; Nakata, Masanobu; Mizuno, Noriyoshi; Nishitani, Yoshihiro; Komatsuzawa, Hitoshi
Abstract: Streptococcus mutans, a cariogenic pathogen, adheres to the tooth surface and forms a biofilm. Bacterial cell surface proteins are associated with adherence to substrates. Sortase A (SrtA) mediates the localization of proteins with an LPXTG motif‐containing proteins to the cell surface by covalent binding to peptidoglycan. In S. mutans UA159, six SrtA‐dependent proteins, SpaP, WapA, WapE, DexA, FruA, and GbpC, were identified. Although some of these proteins were characterized, a comprehensive analysis of the six proteins has not been reported. In this study, we constructed mutants deficient in each of these proteins and the SrtA‐deficient mutant. The SrtA‐deficient mutant showed drastically decreased binding to salivary components, biofilm formation, bacterial coaggregation activity, hydrophobicity, and cellular matrix binding (collagen type I, fibronectin, and laminin). The SpaP‐deficient mutant showed significantly reduced binding to salivary components and partially increased coaggregation with Porphyromonas gingivalis, and decreased hydrophobicity, and collagen binding. The WapA‐deficient mutant showed slightly decreased coaggregation with Fusobacterium nucleatum . Although the SrtA‐deficient mutant showed drastically altered phenotypes, all SrtA‐dependent protein‐deficient mutants, except the SpaP‐deficient mutant, did not show considerable alterations in binding to salivary components. These results indicate that the six proteins may coordinately contribute to these activities. In addition, using genomic data of 125 S. mutans strains, the amino acid sequences of each surface protein were compared and many variations were found among strains, which may affect the phenotype of cell surface proteins in S. mutans .